2000
DOI: 10.1073/pnas.97.4.1566
|View full text |Cite
|
Sign up to set email alerts
|

RANK is the intrinsic hematopoietic cell surface receptor that controls osteoclastogenesis and regulation of bone mass and calcium metabolism

Abstract: We have generated RANK (receptor activator of NF-B) nullizygous mice to determine the molecular genetic interactions between osteoprotegerin, osteoprotegerin ligand, and RANK during bone resorption and remodeling processes. RANK ؊/؊ mice lack osteoclasts and have a profound defect in bone resorption and remodeling and in the development of the cartilaginous growth plates of endochondral bone. The osteopetrosis observed in these mice can be reversed by transplantation of bone marrow from rag1 ؊/؊ (recombinase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
692
1
24

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,015 publications
(731 citation statements)
references
References 28 publications
14
692
1
24
Order By: Relevance
“…For example, one possible candidate gene on chromosome 18q21 is the TNFRSF11A gene, which encodes receptor activator of nuclear factor B (RANK). RANK has been shown to be critically involved in the differentiation of osteoclasts in inflamed synovium and is clearly important for the development of bone resorption in inflammatory arthritis (39). Because the NARAC collection is specifically selected for erosive RA, our patient population is well suited to detect genes involved in the pathogenesis of bony erosions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one possible candidate gene on chromosome 18q21 is the TNFRSF11A gene, which encodes receptor activator of nuclear factor B (RANK). RANK has been shown to be critically involved in the differentiation of osteoclasts in inflamed synovium and is clearly important for the development of bone resorption in inflammatory arthritis (39). Because the NARAC collection is specifically selected for erosive RA, our patient population is well suited to detect genes involved in the pathogenesis of bony erosions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have shown that TNFa may promote the osteolysis of aseptic loosening by directly inducing arthroplasty-derived macrophages to differentiate into osteoclasts. A role for TNFa stimulation of osteoclast formation was suggested by the studies of Li et al who found that TNFa treatment leads to the formation of osteoclasts near the site of injection in RANK knockout mice (RANK-/-) which have a form of osteopetrosis characterized by an absence of osteoclasts [34]. It has recently been found that MNCs expressing the cytochemical characteristics of osteoclasts can be formed from mouse marrow precursors in the presence of M-CSF when TNFa is substituted for RANKL [26], but that these MNCs are not capable of lacunar resorption unless 1L-lr is also present.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between RANKL and RANK is critical in the formation and activation of osteoclasts, and inhibition by OPG results in inhibition of bone resorption. The critical role of these TNF family members is highlighted by in vivo studies where mice deficient in RANK or RANKL have extensive osteopetrosis due to a lack of functional osteoclasts (17,18), whereas OPG knock out mice have severe osteoporosis (19).…”
Section: The Rank/rankl/opg Systemmentioning
confidence: 99%